DESIGN AND SAFETY ANALYSIS OF A NAVAL REACTOR FOR NUCLEAR POWERED SHIP - HOQUE JUWEL, MUHAMMAD MONIRUL (Department of Nuclear Science and Engineering, MIST, 2022)
The development of alternate sources of propulsion power is necessary because of the increasing demand for electricity, environmental concerns, the strain on fossil fuels, as well as pollution prevention and carbon emission control. Hence, in order to optimize propulsion power, it is decided in this study aims to present a nuclear naval small modular reactor in an existing merchant ship. The main idea is to reconsider whether nuclear propulsion is appropriate for merchant ships. Finally, the operational economics of nuclear ships have been compared to those of diesel ships. After a comparison of the available nuclear reactors, the KLT-40S small modular reactor is chosen due to its smaller size, lower power, and higher safety standards. Criticality analysis of the MONK simulation findings indicates that the KLT-40S reactor core is capable of operating for a 10-year period without refueling. The crews' necessary safety needs have been the subject of safety analysis, and additional safety measures for the marine nuclear environment have been recommended. Based on Rad Pro simulations, a plausible shield's safety design is proposed. In this study, it is found that a reactor shield made of 100 cm of polyethylene and 30 cm of lead worked better than steel at limiting radiation rates to 1 mSv/h. A performance evaluation tools model, which permits comparison of the nuclear commercial ship to a ship fueled by diesel, is used to examine the economic viability of the vessel. Finally, it can be concluded that, even with conservative assumptions about a high fuel price and capital cost, a nuclearpowered ship is a workable substitute for a diesel ship throughout the course of the ship's lifetime.
First of all, I want to thank Almighty Allah for bestowing gifts on me, but more importantly for blessing us with such a wondrous nature, full of surprises and opportunities. I would like to thank my thesis supervisor, Dr. Md. Reaz Hasan Khondoker, PEng., Professor ofNaval Architecture and Marine Engineering Department, Military Institute of Science and Technology for his patience, guidance, advice, support and leading me on this adventure. I would also like to thank my thesis co-supervisor, Dr. Ruhul Amin Khan, Director and Chief Scientific Officer of Institute of Radiation and Polymer Technology, Bangladesh Atomic Energy Commission, Savar, Dhaka for his enthusiasm to support me to achieve my academic goals. I would like to express deep gratitude to Head of Nuclear Science and Engineering Department for his insightful criticisms, constant availability, insights into all facets of the research, and creation of a nurturing environment for me since my arrival at the Military Institute of Science and Technology. I am grateful to my parents for their support and affection. I would like to express my gratitude to my wife, Ms. Nargis Akter, for her continuous support. Finally, thanks to the faculty members, staff and friends of Nuclear and Science Engineering Department, Military Institute of Science and Technology for making my time there a greatly rewarding one. I wish to thank Military Institute of Science and Technology for the valuable opportunity to perform this research.